The Oxford handbook of business and government - Coen, David; Grant, Wyn; Wilson, Graham K.
This text provides an introduction to the ways in which five different disciplines have approached the study of business and government. It examines how business interacts with government in different parts of the world, including the United States, the EU, China, Japan and South America.